Quantifying the stress of the Saturnian magnetosphere during the Cassini era - Staniland,N; Dougherty,M; Masters,A (Geophysical Research Letters, 2018)
We quantify the magnetospheric stress state of Saturn, revealing the nature of the planetary environment and its current systems. The complete magnetic field data set collected by the Cassini spacecraft is used to track the global behavior of the Saturnian magnetosphere during the Cassini era. Variations in the magnetodisc current model parameter μoIo determine when the system is stretched, compressed, or near the ground state. Of the 111 orbits that pass through our chosen region, 69 are well described by the model, indicating a steady state current sheet during this interval. While the stress state displays a dependence on local time, it is also shown to vary temporally. We conclude that the Saturnian magnetosphere remained in a quiet state for a significant period of the Cassini orbital mission at Saturn, with occasional largescale deviations observed.